Episodes from the Early History of Mathematics - Aaboe, Asger (1964)
5-33, fig. 1.1-1.8: Babylonian Mathematics: 1.1 Sources; 1.2 The Babylonian Number System. A Multiplication Table; 1.3 The Babylonian Number System. A Table of Reciprocals; 1.4 Positional Number Systems; 1.5 Babylonian Arithmetic; 1.6 Three Babylonian Mathematical Texts; 1.7 Summary.